Faktor-Faktor yang Mempengaruhi Nilai Perusahaan - Dede Abdul Rozak; Mohamad Apip; Rifki Abdul Malik (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2026)
Amidst complex market share dynamics, manufacturing companies particularly those in the cosmetics sub-sector—are compelled to enhance their corporate value. However, high corporate growth, capital structure, and profitability do not necessarily lead to a consistent increase in corporate value. This study aims to identify the variables that—both partially and simultaneously influence the corporate value of PT Unilever Tbk, a company listed on the Indonesia Stock Exchange (IDX), during the 2010–2021 period. PT Unilever Tbk was selected as the sample for this study from the cosmetics manufacturing sub-sector. The sample was chosen using purposive sampling based on predetermined criteria. Data processing was conducted using SPSS version 25, and analysis was performed using multiple regression. The findings indicate that, between 2010 and 2021, profitability had a substantial positive impact on the corporate value of PT Unilever Tbk on the IDX, whereas capital structure and business expansion had a negligible impact. Furthermore, the results show that corporate growth, capital structure, and profitability did not have a statistically significant impact on the corporate value of PT Unilever Tbk on the IDX during the 2010–2021 period.